How common is the common good? Moving beyond idealistic notions of deliberative democracy in education - Knowles, Ryan T.; Clark, Christopher H. (Teaching and Teacher Education, 2018)
Assumptions based on deliberative democratic theory have dominated scholarship of democratic citizenship within political science and educational research. However, both fields have produced scholarship that raises questions regarding the efficacy of the deliberative model of democratic education. This article presents a critical synthesis that highlights the major trends of deliberative democratic theory from the field of political science, while making connections to education specific literature. The shift, away from idealistic notions toward a model of deliberative democracy that considers identity, group interests, and power differences within society, supports similar efforts to revisit democratic theory within civic education. The article concludes with recommendations for a revised, more realistic, conceptualization of civic education.
Keywords: Civic education; Deliberative democracy; Democratic citizenship; Social studies education